Evaluasi Proses Sistem Rujukan Jaminan Kesehatan Nasional Pada Fasilitas Kesehatan Tingkat Pertama (FKTP) : Literatur Review - Anisya Febriyanti; Muhammad Fawwaz; Tania Rahmayanti; Novita Dwi Istanti (Lembaga Pengembangan Kinerja Dosen, 2023)
UUD 1945 that the government must provide a sense of well-being and health to all members of society, this is implemented in the National Health Insurance implemented by the Health Social Security Administration Agency (BPJS). FKTP is at the forefront of providing health services in Indonesia. This study aims to evaluate the national health insurance referral system at FKTP. The research design used in this study was a literature review using Google scholar to search for previous related articles. The related article criteria used were those published from 2017-2023 and collected as many as 6 journals. Based on the six journals, the results show that the National Health Insurance Referral system at First Level Health Facilities (FKTP) has been running well in the community even though in its implementation there are still deficiencies in FKTP.